Clothing Brands’ Sustainability Practices: A Bibliometric Approach - Md Abu Hasan; Saurav Chandra Talukder; Zoltán Lakner; Ágoston Temesi (Administrative Sciences)
The clothing industry greatly impacts the global economy by producing billions of pieces of clothing and employing millions. However, it negatively impacts the environment, as it is one of the most polluting sectors in the world. This bibliometric review aims to identify influential authors and affiliations, journals, productive and cited countries, emerging and recent themes, and future research directions focusing on the dynamics of clothing brands’ sustainability practices. A comprehensive dataset from Scopus and the Web of Science contains 612 articles, and Biblioshiny and VOSviewer were used to analyze the data. Findings reveal that sustainability is not just a concern for developed countries but is also gaining attention in emerging economies like India. This bibliometric analysis presents its relationship with sustainable development goals (SDGs), combines performance analysis and science mapping of clothing brands’ sustainability practices, and evaluates thematic clusters to highlight future research scopes to fill the literature gap for further concentration on behavioral aspects, advanced supply chains, effective communication, and promoting the usage of sustainable technologies, which can help to align with business models for sustainability and resilience. Therefore, clothing brands’ sustainability practices should focus on smart and functional clothing through eco-friendly manufacturing and designing long-lasting clothes to enrich clothing performance. They should adopt innovative technologies for resource utilization, recycling, waste management, supply chain, and also emphasize communication with the consumers to encourage them to purchase eco-friendly and long-lasting clothes.